Redox balance in dairy cattle and their calves at birth and its relationship to colostral passive immunity - Gökçe, E; Cihan, P; Kuru, M; Atakişi, O; Erkılıç, EE; Makav, M; Erdogan, HM (Journal of the Hellenic Veterinary Medical Society, 2025)
Newborn calves are exposed to oxidative stress (OS) just after birth, and yet the role of colostrum in OS is not well detailed. The redox indicators [total antioxidant status (TAS), total oxidant status (TOS) and oxidative stress index (OSI)] and immunoglobulin-G (IgG) concentration in 21 Swiss Brown healthy mother and their calves were measured and changes in the same parameters and IgG concentrations in 23 healthy calves in the first 45 days of life (day 0 = at birth, 1, 3, 7, 14, 28 and 45) were evaluted. TAS and TOS concentrations were determined calorimetrically and IgG level by commercial ELISA kit. A negative correlation was determined between colostral IgG and serum maternal TOS (r:-0.49, P<0.05) and colostral TAS (r:-0.54, P <0.05). In calves, TOS (8.29±0.30), TAS (0.71 ± 0.02) and OSi (1.20 ± 0.08) levels were high at birth, it decreased after the 24th hour (6.72±0.2, 0.65 ± 0.03, and 1.05 ± 0.05, respectively) and remained stable during the study. The number of animals used is relatively small for a safe assumption. However, results may suggest that newborn calves experince OS after birth and colostrum may be an important source of antioxidants against OS.